Development and characterization of microsatellite loci of microglanis cottoides (siluriformes: pseudopimelodidae) and cross-species amplification - Souza-Shibatta, Lenice; Ferreira, Dhiego Gomes; Oliveira, Claudio [UNESP]; Almeida, Fernanda Simoes de; Shibatta, Oscar Akio; Sofia, Silvia Helena (Soc Brasileira Ictiologia, 2013)
Thirteen microsatellite loci were isolated and characterized in Microglanis cottoides. Of these, two were monomorphic and 11 were polymorphic. These polymorphic loci tested on 24 individuals from a wild population produced a total of 108 different alleles, with levels of variability high, ranging from 2 to 20, with an average of 8.3 alleles per locus. The observed and expected heterozygosity ranged from 0.125 to 0.958 and from 0.119 to 0.931, respectively. A high combined probability of paternity exclusion value and a low probability combined genetic identity value obtained show that the set of loci described herein displays good suitability for paternity studies and differentiation of M. cottoides. Additionally, all thirteen microsatellite primers developed for M. cottoides were tested in four other Pseudopimelodidae species and successful cross-species amplification was achieved for the majority of loci.
Keywords: Brazilian Eastern basin; Catfish; Enriched genomic library; Genetic marker; SSR